Prevalence, risk factors and quality of life impact of urinary incontinence in pregnancy at a northcentral Nigerian tertiary hospital - Sulaiman, Bilal; Omonua, Kate I.; Obanimoh, Anthony; Audu, Linda J.; Ahmed, Rabiat M.; Shuaibu, Yusuf; Gambo, Amina U.; Nasir, Sadiya; Isah, Aliyu Y. (International Journal of Research in Medical Sciences, 2025)
Background: Urinary incontinence during pregnancy is a distressing but often under-recognized condition with physical, psychological, and social consequences. Despite its impact, UI remains underreported and underexplored in Nigeria. This study aimed to determine the prevalence, risk factors, and quality-of-life impact of urinary incontinence among pregnant women attending antenatal care at a tertiary hospital in Northcentral Nigeria. Methods: This was a cross-sectional study conducted among 959 pregnant women attending antenatal care at University of Abuja Teaching Hospital, Abuja. Eligible participants completed a structured questionnaire, including the International Consultation on Incontinence Questionnaire–Urinary Incontinence Short Form (ICIQ-UI-SF). Data were analysed using SPSS v25. Associations were tested with chi-square and logistic regression, with significance set at p<0.05. Results: The mean age was 31.1±5 years, and the prevalence of UI was 14.1%. Stress urinary incontinence was most common (54.6%), followed by mixed (20.0%) and urge (18.5%). Most cases were mild (58.5%), though 15.4% were severe. Independent predictors included single marital status (aOR=2.76), occupation (civil servant aOR=2.21; business aOR=1.98), instrumental delivery (aOR=2.85), neonatal birthweight ≥3.6 kg (aOR=8.90), perineal injury (aOR=6.12), and chronic cough (aOR=4.21). Conclusions: UI affects a notable proportion of pregnant women, predominantly as stress incontinence of mild severity. Key risk factors span sociodemographic, obstetric, and clinical domains. Incorporating routine screening, pelvic floor education, and preventive strategies into antenatal care could mitigate the burden and improve maternal quality of life.